2021
DOI: 10.1038/s41467-020-20477-6
|View full text |Cite
|
Sign up to set email alerts
|

Avalanche criticality during ferroelectric/ferroelastic switching

Abstract: Field induced domain wall displacements define ferroelectric/ferroelastic hysteresis loops, which are at the core of piezoelectric, magnetoelectric and memristive devices. These collective displacements are scale invariant jumps with avalanche characteristics. Here, we analyse the spatial distribution of avalanches in ferroelectrics with different domain and transformation patterns: Pb(Mg1/3Nb2/3)O3–PbTiO3 contains complex domains with needles and junction patterns, while BaTiO3 has parallel straight domains. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 65 publications
3
24
0
Order By: Relevance
“…Under stress, the domain walls do no longer move smoothly, but form avalanches. This phenomenon is rather common when walls de-pin and nucleate new walls, see the reviews in [16,[42][43][44][45][46]. The energy distributions of these avalanches follow power laws with energy exponents ε between 1.33 and 2.7.…”
Section: Twin Walls As Storages For Cations and Their Pinning Behaviour In Anorthoclasementioning
confidence: 96%
“…Under stress, the domain walls do no longer move smoothly, but form avalanches. This phenomenon is rather common when walls de-pin and nucleate new walls, see the reviews in [16,[42][43][44][45][46]. The energy distributions of these avalanches follow power laws with energy exponents ε between 1.33 and 2.7.…”
Section: Twin Walls As Storages For Cations and Their Pinning Behaviour In Anorthoclasementioning
confidence: 96%
“…Avalanche dynamics also describe the fluctuations of stock markets, which have small fluctuations and stock disasters caused by financial crisis [6], the temporary evolution of neuron connectors during 'thinking' processes [13][14][15], and the medical deterioration of brain structures [16,17]. Other examples are the Barkhausen 'noise' of pinned domain walls during magnetization processes [18][19][20][21], martensitic transformations [22,23], plastic deformation in solids [24], materials failure [25], ferroelectric and ferroelastic domain movements [3,[26][27][28][29] etc. Avalanche events are monitored by different monitoring methods, such as force drop measurement [30], optical observation [28], thermal radiation observation [23], etc.…”
Section: Avalanches and Acoustic Emission Spectroscopymentioning
confidence: 99%
“…Other examples are the Barkhausen 'noise' of pinned domain walls during magnetization processes [18][19][20][21], martensitic transformations [22,23], plastic deformation in solids [24], materials failure [25], ferroelectric and ferroelastic domain movements [3,[26][27][28][29] etc. Avalanche events are monitored by different monitoring methods, such as force drop measurement [30], optical observation [28], thermal radiation observation [23], etc.…”
Section: Avalanches and Acoustic Emission Spectroscopymentioning
confidence: 99%
“…The unique aspect is that geometrical patterns can be observed, e.g., in optical microscopy, and their evolution can be measured. It was found that the changes of pattern are often fractal and that direct anticorrelations between the Hausdorff dimension of the pattern evolution and the avalanche scaling of their energies or amplitudes were observed [34]. So far, these observations are empirical and do not distinguish between exponents of dynamical processes and topological configurations, but it is anticipated that with the advent of more experiments with much higher time and space resolution, the detailed characterization of the pattern formation process will advance further.…”
Section: Introductionmentioning
confidence: 99%
“…Avalanches in BaTiO 3 have the advantage that the Hausdorff dimension of the emerging domain patterns can be evaluated directly by optical observations [34]. Our model is designed to answer the question: What pattern evolution is expected during porous collapse and what correlations exist between dynamic avalanche parameters (e.g., the exponents of power law distributions), the collapse pattern, and the Hausdorff dimension.…”
Section: Introductionmentioning
confidence: 99%